Accidentally Amy - Painter, Lynn (Berkley Romance, 2025)
"A stolen latte results in a meet-cute for the ages in this originally self-published, brand-new edition of New York Times bestselling author Lynn Painter's rom-com Accidentally Amy, with bonus content. Isabella Shay is usually a very honest person. But when she's running late for her first day at her dream job and the barista yells for "Amy" three times with no answer, she does the unthinkable. Izzy takes that PSL. It's the exact drink she ordered and paid for, only way further ahead in the queue--and she'll take whatever bad karma is coming for her; she's desperate and very late. But when she turns around and runs directly into the most attractive man she's ever seen, spilling the drink all over his made-for-GQ shirt and tie, she ends up having the ultimate meet-cute. Karma who? Sparks fly and things feel beyond promising, until he says to her: "See you tomorrow, Amy." Izzy reasons she can just straighten things out the next day, no biggie. Only when she gets to her new office and meets the VP of her department, it is none other than Blake Phillips--the hottie from Starbucks. And the man might've been charming to "Amy," but he is an arrogant grump to Izzy, an arrogant grump who does not find her explanation funny at all. But day by day, an attraction simmers between them and they'll have to find a way to work together without ripping each other's heads--or clothes-off"--